2020
DOI: 10.1155/2020/8825625
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Differences in the Gas Diffusion and Migration Characteristics of Soft and Hard Coal in High Gas Coal Seams

Abstract: At the present time, it is of major significance to examine the differences in the gas diffusion and migration characteristics of soft and hard coal in order to prevent and control safety hazards in high gas coal seams. In this study, the differences in the gas diffusion and migration characteristics between soft coal and hard coal were examined in detail using macrostructural, mesostructural, and microstructural research methods. The root causes of the differences in the gas diffusion and migration between so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A large number of cases have proven that mining the protective coal seam is an effective measure to reduce the gas pressure in the protective coal seam and improve the permeability of the coal seam 33 – 35 . After the protective layer is mined, the gas pressure in the coal seam obviously changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of cases have proven that mining the protective coal seam is an effective measure to reduce the gas pressure in the protective coal seam and improve the permeability of the coal seam 33 – 35 . After the protective layer is mined, the gas pressure in the coal seam obviously changes.…”
Section: Resultsmentioning
confidence: 99%
“…After the protective layer is mined, the gas pressure in the coal seam obviously changes. According to the research results of Yuanliang, an academician at the Chinese Academy of Engineering 35 , the gas pressure in the protected layer obviously changed before and after mining of the protective layer, and the measured minimum gas pressure was 0.2 MPa (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The surface area of soft coal is 1.6 times that of hard coal. At the same time, the gas adsorption capacity of soft and hard coal is also different. Yuan studied in detail the characteristics of gas diffusion and migration between soft and hard coal from three research perspectives of macrostructure, mesostructure, and microstructure and explored the root cause of the difference in gas diffusion and migration. For the macroscopic structure, the particles of soft coal are flaky and nail shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been indicated that the inflection point of the low-temperature liquid nitrogen adsorption will be advanced following tectonic activities, with the coal tending to have smaller average pore sizes and higher adsorption pore volumes and pore-specific surface areas. Moreover, the adsorption capacity of the coal following increased tectonic activities has been found to be significantly higher than that of indigenous coal of the same coal grade [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%